2023
DOI: 10.1123/jsr.2022-0188
|View full text |Cite
|
Sign up to set email alerts
|

Priming Effects of Anodal Transcranial Direct Current Stimulation on the Effects of Conventional Physiotherapy on Balance and Muscle Performance in Athletes With Anterior Cruciate Ligament Injury

Abstract: Context: In athletes, postural control impairment and knee muscle dysfunction are the most common disorders following anterior cruciate ligament (ACL) injury. Because of functional changes in the motor cortex following ACL injury, physiotherapy (PT) is not enough for treatment and using neuromodulators, such as trans-cranial direct current stimulation (tDCS) may be necessary. The present study focused on the effects of anodal tDCS (a-tDCS) over the primary motor cortex (M1) concurrent with PT on postural contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Postural control is dependent on body balance, a fundamental requirement for movement and activities of daily living [1,45]. Previous research [46,47] has indicated that the negative consequence of decreased balance ability due to fatigue is an increased risk of ankle injury, which accounts for nearly 26% of sports injury types.…”
Section: Effect Of Kt On Static Balancementioning
confidence: 99%
“…Postural control is dependent on body balance, a fundamental requirement for movement and activities of daily living [1,45]. Previous research [46,47] has indicated that the negative consequence of decreased balance ability due to fatigue is an increased risk of ankle injury, which accounts for nearly 26% of sports injury types.…”
Section: Effect Of Kt On Static Balancementioning
confidence: 99%